Evaluation of integrals through psi function - Ramesh Kumar Muthumalai (Scientia, 2025)
Some integrals involving various combinations of elementary functions with psi function are evaluated through elementary methods on properties of psi function. In addition, evaluation of integrals involving various combinations of trigonometric and hyperbolic functions with elementary functions are shown.